STUDI EMPIRIS PENGARUH PENGEMBANGAN KARIR, KOMPENSASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI - Rala, Taufan; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to examine in depth the influence of career development, compensation, and organizational commitment on employee performance through a literature review approach. The method employed is a literature review using the SPIDER framework, encompassing empirical studies published between 2020 and 2025. The findings indicate that career development contributes to improving employee performance by enhancing motivation, self-development opportunities, and career path clarity. Fair and workload-appropriate compensation has been proven to increase productivity and job satisfaction. Meanwhile, organizational commitment plays a crucial role in fostering loyalty, emotional engagement, and a sense of responsibility among employees toward institutional goals. These three variables are interrelated in creating a conducive and performance-oriented work environment. The findings emphasize the importance of integrative human resource management in sustainably supporting employee performance.